Using Artificial Intelligence (AI) In Improving Students’ Writing Ability On Descriptive Text At Grade Eight Of SMP Negeri 1 Siantar - Purba, Dwi Natalia; Herman, Herman; Marpaung, Tiarma Intan (Lembaga Riset dan Inovasi Almatani, 2026)
This research aimed to investigate the effect of using Artificial Intelligence (AI), specifically Grammarly, in improving students’ writing ability on descriptive text at Grade VIII of SMP Negeri 1 Siantar in the academic year 2024/2025. Writing is one of the most challenging skills in English learning, particularly for junior high school students who often face difficulties in grammar, vocabulary, and idea organization. Therefore, the integration of AI-based learning tools is expected to support students in enhancing their writing performance. This study employed a quantitative research method with a quasi-experimental design. The population consisted of 256 Grade VIII students, and the sample was taken using purposive sampling technique. Two classes were selected, namely VIII-1 as the experimental class (32 students) taught using Grammarly, and VIII-2 as the control class (32 students) taught using conventional methods. The data were collected through pre-test and post-test writing assessments and analyzed using the Mann-Whitney U test. The findings revealed that there was a significant improvement in the experimental class after the treatment. The mean score increased from 57.97 in the pre-test to 81.25 in the post-test. Moreover, the result of the Mann-Whitney U test showed a significance value of 0.000, which is lower than 0.05, indicating a significant difference between the experimental and control classes. This proves that Grammarly as an AI-based tool has a significant effect on students’ writing ability in descriptive text. In conclusion, the use of Artificial Intelligence (AI), particularly Grammarly, is effective in improving students’ writing skills. It helps students enhance grammar accuracy, vocabulary usage, and writing confidence. Therefore, AI-based tools are recommended as an innovative learning media in teaching English writing.